SC38 Resuscitation interventions and procedures simulation (RIPS) course – a novel combination of simulation and skills-based training for emergency medicine teams. (3rd November 2019) - Cann, Christopher; Rowland, Emma; Ni-Longain, Niamh
Abstract : Emergency medicine is a growing specialty and as hospital services become increasingly centralised, emergency physicians are expected to perform several rare, time-critical procedures if speciality teams are unavailable. The Royal College of Emergency Medicine curriculum highlights these procedures and, given their low incidence, recommends that simulation is used as a way to develop the skills. In development of this course there were 4 key curriculum areas identified that were not being covered on mandatory courses: Major maxillofacial trauma Obstetric cardiac arrest and neonatal resuscitation Can't intubate, can't oxygenate Traumatic cardiac arrest At the time of writing, the only courses that tried to address these topics were skills based cadaveric courses and, while they may aid the technical skills training, they do not address the human factor elements of these complex cases. Likewise, these courses have limited appeal to nursing staff however nursing familiarity and input in these situations is key to optimal management. The RIPS course was developed to address these issues. Educational theory was used to develop the course structure. A course handbook was developed with multi-speciality input with a focus on simplifying the procedures to the key steps. On the day, an initial lecture introduces human factors with a focus on critical decision making. These concepts are given context and are interleaved into subsequent debriefs. The candidates are split into multidisciplinary teams for the scenarios which utilised customised simulation models to increase fidelity. Debriefs were followed by workshops on the specific procedural steps and allowed time for deliberate practice and feedback. A pilot course was run in 2018. Participants showed statistically significant increases in confidence in all areas. Qualitative feedback highlighted the benefits of having both doctors and nurses and a focus on human factor elements during debriefs. There were suggested improvements around the timing and structure of the course which have been developed and incorporated allowing more time to focus on the area's participants found most beneficial. This year, four RIPS courses have been organised and are fully booked by 60 candidates with an extensive waiting list. By November we will be able to present the feedback from these days and hope to be able to discuss the development of additional faculty with plans to run this course in additional centres. References: RCEM, Curriculum and Assessment Systems for Training in Emergency Medicine, 2015, https://www.rcem.ac.uk/docs/Training/RCEM_2015_Curriculum___Applicable_from_August_2016__approved_23_Nov_2015_ATCF_RTT_DRE-EM_additions_July2017%20-%20JCST%20amendments.pdf, accessed May 2019